Judicial Strategies in Addressing Domestic Violence: Gender-Responsive Legal Analysis from the Religious Court of Malang Regency, Indonesia - Meisy Fajarani; Musleh Harry; Muhammad Jihadil Akbar; Nur Jannani; Mikdar Rusdi (Justicia Islamica, 2026)
This study aims to analyze judicial efforts to enhance protection for women and children in cases of domestic violence, particularly in the Malang region of East Java, where the number of cases has been increasing annually. The methodology employed is legal research using a case study approach, involving data collection through interviews with judges and analysis of court rulings. The results of the study indicate that judges at the Malang Regency Religious Court have developed various strategies to provide more effective protection, particularly in cases involving gender discrimination and DV. These strategies include the fair and prudent application of the law, consideration of the interests of victims and children, and a holistic, comprehensive approach to adjudication. In adjudicating cases, judges refer to various legal instruments, including Law No. 23 of 2004 concerning the Elimination of Domestic Violence and the Compilation of Islamic Law. Practically, this study serves as a reference for policymakers and judicial officials, particularly judges within the Religious Courts, to enhance sensitivity toward gender issues and improve the effectiveness of handling domestic violence cases, thereby further strengthening legal protection for women and children.